Comparison of falls and cost-effectiveness of the group versus individually delivered Lifestyle-integrated Functional Exercise (LiFE) program: final results from the LiFE-is-LiFE non-inferiority trial. (23rd January 2023) - Jansen, Carl-Philipp; Gottschalk, Sophie; Nerz, Corinna; Labudek, Sarah; Kramer-Gmeiner, Franziska; Klenk, Jochen; Clemson, Lindy; Todd, Chris; Dams, Judith; König, Hans-Helmut; Becker, Clemens; Schwenk, Michael
Abstract: Background: the individually delivered Lifestyle-integrated Functional Exercise (LiFE) was shown to improve physical activity (PA) and reduce fall incidence, however being rather resource-consuming due to one-to-one delivery. A potentially less resource-intensive group format (gLiFE) was developed and compared against the original program, considering higher risk of falling due to possible PA enhancement. Objective: to investigate non-inferiority in terms of PA-adjusted fall risk and cost-effectiveness of gLiFE at 12-month follow-up. Design: single-blinded, randomised, multi-centre non-inferiority trial. Setting: community. Subjects: in total, 309 adults aged 70+ years at risk of or with history of falling; n  = 153 in gLiFE, n  = 156 in LiFE. Methods: LiFE was delivered one-to-one at the participants' homes, gLiFE in a group. PA-adjusted fall risk was analysed using negative binomial regression to compare incidence rate ratios (IRR). Cost-effectiveness was presented by incremental cost-effectiveness ratios and cost-effectiveness acceptability curves, considering quality-adjusted life years, PA and falls as effect measures. Secondary analyses included PA (steps/day) and fall outcomes. Results: non-inferiority was inconclusive (IRR 0.96; 95% confidence interval, CI 0.67; 1.37); intervention costs were lower for gLiFE, but cost-effectiveness was uncertain. gLiFE participants significantly increased PA (+1, 090 steps/day; 95% CI 345 and 1.835) versus insignificant increase in LiFE (+569, 95% CI −31; 1, 168). Number of falls and fallers were reduced in both formats. Conclusion: non-inferiority of gLiFE compared with LiFE was inconclusive after 12 months. Increases in PA were clinically relevant in both groups, although nearly twice as high in gLiFE. Despite lower intervention costs of gLiFE, it was not clearly superior in terms of cost-effectiveness.